2013
DOI: 10.1039/c3cc00235g
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional mesoporous silica nanoparticles as cooperative catalysts for the Tsuji–Trost reaction – tuning the reactivity of silica nanoparticles

Abstract: Bifunctional mesoporous silica nanoparticles (MSNs) bearing Pd-complexes and additional basic sites were prepared and tested as cooperative active catalysts in the Tsuji-Trost allylation of ethyl acetoacetate. Functionalization of the MSNs was realized by postmodification using click-chemistry. The selectivity of mono versus double allylation was achieved by control of reaction temperature and the nature of the catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 19 publications
(3 reference statements)
0
47
0
Order By: Relevance
“…416,417 The synthesis involved the reactions of APTMSl, followed by the Pd II -[N-(2aminoethyl)-3-aminopropyltrimethoxysilane] complex. 416,417 The synthesis involved the reactions of APTMSl, followed by the Pd II -[N-(2aminoethyl)-3-aminopropyltrimethoxysilane] complex.…”
Section: Metal-base Bifunctional Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…416,417 The synthesis involved the reactions of APTMSl, followed by the Pd II -[N-(2aminoethyl)-3-aminopropyltrimethoxysilane] complex. 416,417 The synthesis involved the reactions of APTMSl, followed by the Pd II -[N-(2aminoethyl)-3-aminopropyltrimethoxysilane] complex.…”
Section: Metal-base Bifunctional Catalystsmentioning
confidence: 99%
“…416,417 The synthesis involved the reactions of APTMSl, followed by the Pd II -[N-(2aminoethyl)-3-aminopropyltrimethoxysilane] complex. 417 The ''mother'' particles bearing two chemical orthogonal functionalities, namely, azides and alkoxyamines were first prepared (Fig. For the bifunctional catalysts derived from different supports, namely MCM-41 and SBA-15, a similar catalytic performance was observed.…”
Section: Metal-base Bifunctional Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerted catalysis between metal complexes and organic functional groups is a notable strategy to create novel heterogeneous catalysis and a highly efficient technique for molecular transformations . Several research groups have reported Pd, Rh, and Cu complexes immobilized on solid surfaces with organic functionalities for the efficient transformation of organic molecules. In the case of concerted catalysis with Pd complexes, the allylation of nucleophiles was shown to be effectively accelerated by the assistance of a basic amine group: both allylic substrates and nucleophiles were activated by Pd complexes and bases, respectively …”
Section: Figurementioning
confidence: 99%
“…The allylic alkylation is a versatile method to construct C-C bonds, especially products with bulky quaternary carbon centres. 6,7 The allyl carbonate and palladium form an η 3 -allylpalladium complex, which is attacked by a nucleophile. In general, C-H acidic compounds are used, but nucleophiles like diphenylmethane are also suitable.…”
Section: Abstracts (A) Allylic Alkylation Of Nucleophiles; C-c Bond Fmentioning
confidence: 99%